DNA double-strand breaks alter the spatial arrangement of homologous loci in plant cells - Hirakawa, Takeshi (Sci Rep, 2015)
Chromatin dynamics and arrangement are involved in many biological processes in nuclei of eukaryotes including plants. Plants have to respond rapidly to various environmental stimuli to achieve growth and development because they cannot move. It is assumed that the alteration of chromatin dynamics and arrangement support the response to these stimuli; however, there is little information in plants. In this study, we investigated the chromatin dynamics and arrangement with DNA damage in Arabidopsis thaliana by live-cell imaging with the lacO/LacI-EGFP system and simulation analysis. It was revealed that homologous loci kept a constant distance in nuclei of A. thaliana roots in general growth. We also found that DNA double-strand breaks (DSBs) induce the approach of the homologous loci with γ-irradiation. Furthermore, AtRAD54, which performs an important role in the homologous recombination repair pathway, was involved in the pairing of homologous loci with γ-irradiation. These results suggest that homologous loci approach each other to repair DSBs, and AtRAD54 mediates these phenomena.